IMPLEMENTATION OF AN EXCLUSIVE BREASTFEEDING POLICY IN WONOGIRI REGENCY - Dewi Nur Pratiwi; Ernawaty (The Indonesian Journal of Public Health, 2023)
Introduction: Breastfeeding is the best intake to fulfill nutrition of babies aged 0-6 months. In Wonogiri Regency, exclusive breastfeeding achievement in 2017 is 53.62% and 25 out of 34 public health centers haven’t reached the target yet. Method:  This research was descriptive research type with observational approach and cross-sectional design. Sample was 34 public health centers in Wonogiri Regency, with nutritionist, midwives and health cadres from each public health centers as respondents. The data were collected using interview and questionnaire techniques, and   correlation analysis performed  using the contingent coefficient method. Result: show that   communication factors showed good result for respondent’s knowledge, consistency in obtaining socialization and transmission to carry out further socialization. Resource factors show  that availability of nutrition staff isn’t sufficient and funds lack for activities related to exclusive breastfeeding. On disposition factors, respondents disagree with the gift provided from the formula milk distributor because it can inhibit achievement of exclusive breastfeeding purpose. And   many public health centers still don’t have exclusive breastfeeding SOP. Conclusion: It can be concluded that training, availability of facilities and infrastructures in lactation room and number of staff    positively affect   target achievement of exclusive breastfeeding. The effort that can be done is by giving counselling of breastfeeding to workers and healthcare staff, fulfillment of facilities and infrastructure of lactation room to support exclusive breastfeeding, making SOP related to breastfeeding for public health centers.